Scanning electron microscopy of mycoplasmas adhering to erythrocytes. - Razin, S (1980)
The interaction of Mycoplasma pneumoniae and Mycoplasma gallisepticum with human erythrocytes (RBC) was studied by scanning electron microscopy. The tight nature of the attachment of the microorganisms to the RBC was indicated by the indentation of the RBC surface at the site of attachment of M. gallisepticum cells and by traction and resulting distortion in the shape of the RBC at the point of its attachment to M. pneumoniae filaments growing on glass or plastic. In many cases attachment took place via the tip of the filaments, the membrane of the parasite appearing to be fused with that of the RBC. The morphology of the mycoplasmas growing on cover slips conformed in general with previous descriptions obtained by scanning electron microscopy. Growth of M. pneumoniae on glass or plastic consisted of branching filaments spread on the inert surface and microcolonies made up of intertwining filaments projecting into the medium. The filaments had a bulbous swelling adjacent to a tapered tip end. A few filaments were shown to have a ropelike helical twist. M. gallisepticum grown on the cover slips of Leighton tubes had a peculiar fusiform or teardrop shape with blebs at one or both poles of the cells. Elongated filamentous forms and chains of coccobacillary bodies were observed as well.